Quantitative imaging of subcellular metabolism with stable isotopes and multi-isotope imaging mass spectrometry - Steinhauser, Matthew L. (2013)
Multi-isotope imaging mass spectrometry (MIMS) is the quantitative imaging of stable isotope labels in cells with a new type of secondary ion mass spectrometer (NanoSIMS). The power of the methodology is attributable to (i) the immense advantage of using non-toxic stable isotope labels, (ii) high resolution imaging that approaches the resolution of usual transmission electron microscopy and (iii) the precise quantification of label down to 1 part-per-million and spanning several orders of magnitude. Here we review the basic elements of MIMS and describe new applications of MIMS to the quantitative study of metabolic processes including protein and nucleic acid synthesis in model organisms ranging from microbes to humans.